Does sacking a coach really help? Evidence from a Difference-in-Differences approach - Fabrício, Gustavo de Souza Machado (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science